PENGARUH KEPEMIMPINAN TRANFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI KASUS PERUMDA TIRTA KHAYANGAN) - Erita Utari; Zusmawati Zusmawati (LP2M Universitas Bina Bangsa, 2024)
The purpose of this research is to examine the influence of transformational leadership and organizational culture on employee performance in Perumda Tirta Khayangan (full river city). The variables used in this research include the dependent variable, namely employee performance (Y), and the independent variables, namely transformational leadership (X1) and organizational culture (X2). This type of research uses a quantitative method, wanting to collect data by distributing questionnaires to 100 respondents using total sampling, namely a non-random sampling technique. By using instrument tests (validity test and reliability test), assumption tests (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of the SPSS application. The results of this research show that transformational leadership has a positive and significant effect on employee work and organizational culture has a positive and significant effect on employee performance